Development of a Minimum Competency Assessment Instrument for Reading Literacy Containing Sasak Local Wisdom in Class V of 33 Mataram State Elementary Schools - Putri, Nanda Sakina; Hariana Intiana, Siti Rohana; Sobri, Muhammad; Ermiana, Ida (Mataram University, 2024)
This research aims to develop a minimum competency assessment instrument for reading literacy containing Sasak local wisdom in class V at SDN 33 Mataram. This research is a type of Research and Development (R&D) research with five stages. Analyze produces an analysis of the needs of students in schools related to assessment instruments that have not yet reached the measurement of reading literacy competency. Design, namely designing assessment instruments by making grids, writing stimuli, writing question items and answer keys, work instructions, and scoring guidelines. Development, namely developing products through the testmoz website and carrying out expert validation. Implementation by testing assessment instruments to determine validity, reliability and practicality and applying them to real classes. Evaluation, testing product effectiveness. The data collection techniques used were interviews, questionnaires, documentation and tests. This research was conducted at SDN 33 Mataram using evaluation and language expert validation sheet instruments, teacher and student response questionnaires, as well as reading literacy assessment instruments. The results of the research show that the minimum competency assessment instrument for reading literacy containing Sasak local wisdom received a percentage of 94.2% from evaluation experts, a percentage of 100% from language experts, a percentage of 97.8% with very practical criteria from teacher responses, a percentage of 91.5% with criteria very practical from the students' responses, getting the results of 23 valid and reliable questions from the results of the analysis of the questions after the trial. Testing effectiveness with a one sample T-test using SPSS 26 with a significance value of 0.000<0.05 means there is a difference in the average student score and the test value. Therefore, it can be concluded based on the research results that the development of a minimum competency assessment instrument for reading literacy containing Sasak local wisdom in class V can be declared valid, reliable, practical and effectively used in measuring students reading literacy abilities.